Kitchen chemistry a teaching sequence for the teaching of colligative properties (Research, Society and Development, 2021)
The present didactic sequence had as objective the elaboration and execution of a didactic sequence with theoretical base in the three pedagogical moments for the teaching of colligative properties. Based on the three pedagogical moments, the activity was elaborated based on the theme "Chemistry in the kitchen", for this in the first pedagogical moment, which is called initial problematization, questions were raised on the subject related to the four main colligative properties: ebullioscopy, tonoscopy, osmotic pressure and cryoscopy. Right after, in the second moment called knowledge organization, the content was exposed in a frame to explain the concept to be learned, based on the hypotheses raised by the students. Furthermore, for the concept of cryoscopy, an investigative experiment was used to organize the student's knowledge. In the last pedagogical moment, the application of knowledge, entrance exam questions and open questions were used in which students should discuss the answers. Thus, after analyzing the data collected, the present teaching tool had an important contribution to the teaching of colligative properties, as it was evidenced that students had an effective learning, and also a contextualized approach favors the debate within the classroom, therefore the student becomes a more critical citizen, who is better positioned to face everyday problems.